A Linguistic Study of Gemination of Arabic Languages - Kadir Mugair (PhD), Sarab (International Journal of Psychosocial Rehabilitation, 2020)
The current research attempts to clarify and distinguish Arabic-determined gemination/doubling ("tashdiid"), especially in two categories: verbs and nouns. The research respects the fundamental etymological assets for clarifying an intensity or richness in the language structure and vocabulary. We can consider the significance of doubling, or what is called tashdiid, in verbs and nouns like one of these sources. The research can also present how these sources are participating in cooperation and what different sorts of unequivocal doubling happen. A current investigation additionally attempts to take into consideration a nuanced explanation of a striking nature of insistent doubling in communicating in Arabic class, i.e., there are different sorts of doubling that had not been heard before that may likewise occur. In this research, the examination uncovered the consequences of a test investigation of the etymological merits of doubled nouns and verbs in Arabic and Iraqi dialects. Current research expects to limit the tentative method of multiplied consonants and, by one way or another, the length of sound doubling, including several Arabic dialects and Iraqi dialect in particular, to disprove the researcher’s perspectives, such as Patai (1973) and Shouby (1970b). To them, the doubling in Arabic dialects could be the misrepresentation procedure that would not become beneficial, which in turn could never advance Arabic dialects at all. A discussion of research displays in general the comprehension of the need for doubling, which permits it to be used as a gainful intelligent asset. Thus, the data of the current examination belongs to Arabic speakers like Jordanian, Syrian, Lebanese, and Iraqi speakers since these dialects could be regarded as neighbor dialects.